Analisis Permendkbudristek No. 46 Tahun 2023 Terhadap Kekerasan Struktural Yang Terjadi Pada Aliran Kepercayaan Sapto Darmo Di Kabupaten Kendal - Surur, Nahar; Nasikhah, Atik Dina; Setyawan, Ego (Jayapangus Press, 2024)
Findings of structural violence in the world of education continue to occur today. One type of structural violence that often occurs in the educational environment is educational discrimination against minorities. Cases of educational discrimination were also experienced by the Sapto Darmo sect of faith in Kendal Regency, some of whom experienced difficulties in obtaining formal education. In fact, Kendal is one of the districts in Central Java Province which has 5 developing religious beliefs, one of which is the Sapto Darmo Belief. The purpose of this research is to find out whether Permendikbudristek Regulation No. 46 of 2023 can be used as a legal umbrella for adherents of the Sapto Darmo belief in Kendal Regency or whether this regulation is just a formality. The method used in this research is analyzing the policy results of Minister of Education and Culture Regulation No. 46 of 2023 on the Sapto Darmo belief sect in Kendal Regency using empirical juridical analysis. In particular, this research is targeted to be a reference source for the Kendal Regency Government in providing equal educational rights for adherents of the Sapto Darmo belief system. The results of this research show that Permendikbudristek No. 46 of 2023 has been implemented well for students who adhere to existing beliefs in Kendal Regency, especially the Sapto Darmo belief sect. The conclusion of this research is that the violence that was previously feared would befall religious students in Kendal Regency has gradually improved and there are no longer any reports of schools prohibiting religious students from entering school. If in the future there are still schools that prohibit this, the Kendal Regency Government and the Kendal Regency Education and Culture Office will seek mediation and legal action.